Sensory profiles are comparable in patients with distal and proximal entrapment neuropathies, while the pain experience differs. (2nd November 2018) - Tampin, Brigitte; Vollert, Jan; Schmid, Annina B.
Abstract: Objective: Distal and proximal entrapment neuropathies such as carpal tunnel syndrome (CTS) and cervical radiculopathy (CR) share similar etiologies. Experimental models suggest that, despite comparable etiology, pathomechanisms associated with injuries of the peripheral and central axon branches are distinct. This study therefore compared self-reported and elicited sensory profiles in patients with distal and proximal entrapment neuropathies. Methods: Patients with electrodiagnostically confirmed CTS ( n = 103) and patients with CR ( n = 23) were included in this study. A group of healthy participants served as controls ( n = 39). Symptoms and sensory profiles were evaluated using quantitative sensory testing (QST) and a self-reported neuropathic pain questionnaire (painDETECT). Results: Both patient groups were characterized by a loss of function in thermal and mechanical detection in the main pain area and dermatome compared to healthy reference data ( p < .001). There was no significant difference between patients with CTS and CR in pain and detection thresholds except for reduced vibration sense in the main pain area ( p < .001) and reduced pressure pain sensitivity in the dermatome in patients with CR ( p < .001). However, patients with CR reported higher pain intensities ( p = .008), more severe pain attacks ( p = .009) and evoked pain by light pressure ( p = .002) compared to patients with CTS. Conclusion: While QST profiles were similar between patients with CTS and CR, self-reported pain profiles differed and may suggest distinct underlying mechanisms in these patient cohorts.